The effective of Using social support sources in Reducing Teachers’ Work Pressure in North Batina Governor in Sultanate of Oman - Al Shibli, Abdullah bin Ali bin Salem (Journal of Educational and Psychological Sciences, 2019)
The purpose of the research is to determine the level of work pressure of a sample of Omani teachers, determine the order of their social support sources. It also, aimed to find out the existence of statistical differences between the sources of social support and the reduce of work pressures according to the educational stage, gender and experience. The study followed the descriptive analytical approach using the different statistical methods to derive the relationship between the independent variable and dependent variables. To achieve the research aims, the researcher used two questionnaires which are the teacher social support measure, which consisted of (36) phrase, and the measure of the work pressure of the teachers, which was consisted of (38) phrase. The study sample was consisted of (291) teachers divided into (136) male teachers and (155) female teachers (3%) of the study population. The results of the study showed the existence of working pressures of Omani teachers in both dimensions with an average of the work pressure (1.77), rated (large). The result revealed that the pressures associated with the learning and learning processes were average (1.79), (large), followed by the pressures associated with the organizational climate at an average of (1.74) in grade (large). The study showed the overall average of social support was (2.50) which estimated at (high).The first level of the social support was assigned to colleagues support and the supervisor support with an average of 2.99, followed by the family support at an average of 2.98 and finally friends support at an average of 2.01.Finally, the results showed that there was no statistically significant differences between the sources of social support and their role in reducing the working pressures of Omani teachers according to the educational stage, gender, and years of experience. According to the previous results, a number of recommendations and proposals were presented to increase the effectiveness of social support and to reduce the pressure of teachers in the Sultanate of Oman and the all Arab Countries.
Keywords: efficacy; Social support sources; work stress